Heparanase and Autoimmune Diabetes - Simeonovic, Charmaine J.; Ziolkowski, Andrew; Wu, Zuopeng; Choong, Fui Jiun; Freeman, Craig; Parish, Christopher (Frontiers in Immunology, 2013)
Heparanase (Hpse) is the only known mammalian endo-β-D-glucuronidase that degrades the glycosaminoglycan heparan sulfate (HS), found attached to the core proteins of heparan sulfate proteoglycans (HSPGs). Hpse plays a homeostatic role in regulating the turnover of cell-associated HS and also degrades extracellular HS in basement membranes (BMs) and the extracellular matrix (ECM), where HSPGs function as a barrier to cell migration. Secreted Hpse is harnessed by leukocytes to facilitate their migration from the blood to sites of inflammation. In the non-obese diabetic (NOD) model of autoimmune Type 1 diabetes (T1D), Hpse is also used by insulitis leukocytes to solubilize the islet BM to enable intra-islet entry of leukocytes and to degrade intracellular HS, an essential component for the survival of insulin-producing islet beta cells. Treatment of prediabetic adult NOD mice with the Hpse inhibitor PI-88 significantly reduced the incidence of T1D by 50% and preserved islet HS. Hpse therefore acts as a novel immune effector mechanism in T1D. Our studies have identified T1D as a Hpse-dependent disease and Hpse inhibitors as novel therapeutics for preventing T1D progression and possibly the development of T1D vascular complications.